Skrining fitokimia dan uji toksisitas ekstrak daun balik angin (Mallotus Sp) terhadap larva Artemia salina Leach dengan metode brine shrimp lethality test (BSLT) - Anderson Arnold Aloanis; Fahriana Fahriana; Haryadi Haryadi (Jurnal Kimia Fullerene, 2017)
One of the plants that are used to regular treatment is behind the wind (Mallotus sp.). Traditionally this is used for the relief of pain and increase stamina by way of boiling the seven pieces of young leaves and drink once a day in the morning. This research aims to know the acute toxicity of ethanol extracts of leaves behind the wind (Mallotus sp) against larvae of Artemia salina Leach BSLT method. The research method used is qualitative analysis of chemical compound and Brine Shrimp Lethality Test (BSLT) method with post-test-only control group design. The results of research on ethanol extracts of leaves behind the wind showed the value of LC50 of 32.061 ppm, so can be said of ethanol extracts of leaves behind the wind on this experiment of acute toxicity has on the larvae of Artemia salina Brine Shrimp method using Leach Lethality Test (BSLT).